Analysis Of Factors Causing Traffic Accidents And Efforts To Prevent Them On The Cross-Sumatera Highway In The Jurisdiction Of The Deli Serdang Police Station - Wahyudi Syahputra; Fitria Ramadhani Siregar (International Journal of Society and Law, 2024)
Traffic accidents that occur are caused by fatigue, carelessness, lack of caution, and negligence experienced by drivers. It is no exaggeration that all traffic accidents involving private vehicles or public vehicles are caused by factors of drivers, pedestrians, vehicles, facilities and infrastructure, officers / law enforcers in road traffic. The legal consequences of traffic accidents are criminal penalties for the creator or cause of the incident and can also be accompanied by civil lawsuits for material losses incurred. In implementing the law, road organizers have faced many obstacles and problems of a technical and non-technical nature. The dominant technical problem is the occurrence of road infrastructure safety deficiencies that have an impact on sub-standard road geometry. Users of heavy goods vehicles that overload and overdimension can accelerate the rate of road damage and interfere with the driver's visibility which has an impact on the chances of a vehicle accident. A significant non-technical problem is the uncontrolled growth of land use around national roads which can interfere with the function and benefits of the road making it difficult to determine the certainty of the level of road service. The problem in this study is about what are the main factors that cause traffic accidents and what can be done to prevent traffic accidents. The research method is by using a type of normative legal research that has a descriptive analysis nature. Using library research techniques (Library Research): namely by collecting and studying and analyzing concepts, opinions or findings and provisions of laws relating to the law. Then analyzed qualitatively to get answers to the problems studied. The results of the study indicate that there are problems related to regulations governing traffic, the implementing regulations of traffic laws have taken too long to be made, in addition to derivative regulations such as regional regulations and other technical instructions that are still not in sync with field conditions, law enforcement factors also dominate the high number of accidents as well as the legal culture that still ignores prioritizing the safety of road users, while efforts to reduce the number of accidents are through efforts to play the role of law enforcement officers in traffic jurisdictions such as the role of the Traffic Police in preventing traffic accidents, while related to legal policies in efforts to overcome criminal acts of traffic accidents that result in the death of victims in the Sat Lantas Polres, it is carried out through Penal, and from the aspect of legal culture, ways to prevent traffic accidents, for example, by implementing the pattern of Do Not Drive Under the Influence. Driving under the influence of alcohol or drugs can reduce your alertness and reaction time.